Efforts to Increase Income of Marlung and Marsus MSMEs through Packaging and Logo Branding: Upaya Peningkatan Pendapatan UMKM Marlung dan Marsus melalui Kemasan dan Branding Logo - Ilham Nur Husnuddin; Afifatus Sholikhah (CV Yazri Aksara Nusantara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in strengthening the national economy, but still face obstacles in increasing competitiveness, especially in the aspect of visual product identity. The low ability of MSME actors to implement branding strategies often causes local products to lose competition in a competitive market. This Community Service activity aims to help MSMEs Marlung and Marsus Warung Al Jaya in Sidoarjo Regency in strengthening product image through the development of packaging designs and logos that are more attractive, informative, and in accordance with business characteristics. The implementation method uses a qualitative descriptive approach with a participatory model, including field observation, needs analysis, design design, training, implementation, and evaluation of results. The results showed a significant increase in the visual appeal of the product, consumer confidence, and an increase in partner revenue by 20–30 percent after the implementation of the new design. In addition to the economic impact, this activity also increases the confidence and ability of business actors to manage brand identity independently. Overall, this activity proves that simple branding-based interventions can strengthen the competitiveness and sustainability of MSMEs in the creative economy era